1998
DOI: 10.1074/jbc.273.32.20383
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Cloning, and Sequence Analysis of the Integrin Subunit α10, a β1-associated Collagen Binding Integrin Expressed on Chondrocytes

Abstract: We have found that chondrocytes express a novel collagen type II-binding integrin, a new member of the ␤1-integrin family. The integrin ␣ subunit, which has a M r of 160 kDa reduced, was isolated from bovine chondrocytes by collagen type II affinity purification. The human homologue was obtained by screening a human chondrocyte library with a bovine cDNA probe. Cloning and cDNA sequence analysis of the human integrin ␣ subunit designated ␣10 show that it shares the general structure of other integrin ␣ subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
161
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(163 citation statements)
references
References 62 publications
1
161
0
1
Order By: Relevance
“…Alternatively to the annexin link, ␣10␤1 integrin function may also be affected by the treatment with collagen peptides. This integrin has been shown to bind to triple-helical collagen type II (55), and it may also interfere with the same signaling pathway. Putative strategies to further clarify the role of the peptide feedback loop in chondrocytes to control ECM turnover will have to consider the various options.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively to the annexin link, ␣10␤1 integrin function may also be affected by the treatment with collagen peptides. This integrin has been shown to bind to triple-helical collagen type II (55), and it may also interfere with the same signaling pathway. Putative strategies to further clarify the role of the peptide feedback loop in chondrocytes to control ECM turnover will have to consider the various options.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of nine integrins incorporates an additional, autonomously folding domain of ϳ200 amino acids, which is inserted between ␤-sheets 2 and 3 of the putative ␤-propeller and is termed the I (inserted) domain. The I domain is present in LFA-1 and the other ␤2 integrins Mac-1, p150,95, and ␣d␤2, as well as in ␣1␤1, ␣2␤1, ␣10␤1, ␣11␤1, and ␣E␤7 (Camper et al, 1998;Dickeson and Santoro, 1998;Velling et al, 1999). The crystal structures of the I domains of LFA-1, Mac-1, and ␣2␤1 have been solved and show a dinucleotidebinding fold (reviewed by Loftus and Liddington, 1997;Humphries and Newham, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This ␤ 1 subunit-containing subclass of integrins is characterized by the presence of an inserted domain (I domain) with homology to von Willebrand factor A domains in their ␣-subunit, which harbors the ligand-binding site (8,9). The integrins ␣ 10 ␤ 1 and ␣ 11 ␤ 1 have a restricted expression pattern on differentiated chondrocytes and developing muscle cells (10,11), whereas ␣ 1 ␤ 1 and ␣ 2 ␤ 1 show a broader distribution, with integrin ␣ 1 ␤ 1 being predominantly expressed by cells of mesenchymal origin and integrin ␣ 2 ␤ 1 by epithelial cells and platelets. In vitro studies suggested an implication of integrin ␣ 2 ␤ 1 in cell attachment and migration (12,13), generation of mechanical forces and contraction of collagen matrices (14), induction of collagenase activity and matrix remodeling (15,16), as well as angiogenesis (17) and epithelial branching morphogenesis (18).…”
mentioning
confidence: 99%